Expectations of Social Consequences Impact Anticipated Involvement in Health‐Risk Behavior During Adolescence. (10th September 2020) - Andrews, Jack L.; Mills, Kathryn L.; Flournoy, John C.; Flannery, Jessica E.; Mobasser, Arian; Ross, Garrett; Durnin, Maureen; Peake, Shannon; Fisher, Philip A.; Pfeifer, Jennifer H.
Abstract : This study examined how individual differences in expectations of social consequences relate to individuals' expected involvement in health‐risk behaviors (HRBs). A total of 122 adolescents (aged 11–17) reported their expected involvement in a number of risk behaviors and whether or not they expect to be liked more or less by engaging in the behavior: the expected social benefit. Higher perceived social benefit was associated with higher anticipated involvement in said behavior. This relationship was stronger for adolescents who reported a higher degree of peer victimization, supporting the hypothesis that experiencing victimization increases the social value of peer interactions. Findings suggest that adolescents incorporate expectations of social consequences when making decisions regarding their involvement in HRBs.